2005
DOI: 10.1200/jco.2005.02.167
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Two Different Doses of Capecitabine in the Treatment of Advanced Breast Cancer in Older Women

Abstract: This study shows that capecitabine is safe and effective in the elderly breast cancer patient. Based on the overall results, the capecitabine dose of 1,000 mg/m(2) twice daily merits consideration as "standard" for older patients who do not have severely impaired renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(120 citation statements)
references
References 20 publications
5
111
1
3
Order By: Relevance
“…There was a steady decrease in the relative dose intensity of capecitabine during treatment caused by treatment delays or dose reductions mostly because of hand -foot syndrome, whereas that of S-1 remained steady (Figure 2). Considering these findings, we suggest that a dose of 1000 mg m À2 two times daily, lower than that recommended, would be appropriate for capecitabine in elderly patients (Bajetta et al, 2005), whereas the recommended dose of 40 mg m À2 two times daily would be acceptable for S-1. These findings suggest that dose escalation of S-1 may be possible in younger patients.…”
Section: Discussionmentioning
confidence: 96%
“…There was a steady decrease in the relative dose intensity of capecitabine during treatment caused by treatment delays or dose reductions mostly because of hand -foot syndrome, whereas that of S-1 remained steady (Figure 2). Considering these findings, we suggest that a dose of 1000 mg m À2 two times daily, lower than that recommended, would be appropriate for capecitabine in elderly patients (Bajetta et al, 2005), whereas the recommended dose of 40 mg m À2 two times daily would be acceptable for S-1. These findings suggest that dose escalation of S-1 may be possible in younger patients.…”
Section: Discussionmentioning
confidence: 96%
“…There were no treatmentrelated deaths, and the most common grade 3 or grade 4 AEs included asthenia, 13% (95% CI, 6%-24%); diarrhea, 10% (95% CI, 4%-20%); vomiting, 6% (95% CI, 2%-16%); and mucositis, 3% (95% CI, 1%-12%), with grade 2 or 3 HFS in 24% (95% CI, 14%-36%) of patients. More recently, Bajetta et al [22] treated 73 patients ≥65 years of age (93% chemotherapy-naïve for metastatic disease) with single-agent capecitabine. The first 30 patients received the standard dose and regimen, but because of two (7%) deaths, both a result of severe dehydration, the investigators decided to reduce the initial capecitabine dose to 1,000 mg/m 2 bid for the next 43 patients (low-dose cohort).…”
Section: Metastatic Disease: First-linementioning
confidence: 99%
“…A phase II RCT by Talbot et al [42] compared the safety profile of single-agent capecitabine with that of singleagent paclitaxel in patients who had failed or were resistant to anthracycline-based therapy and/or who had undergone 19 (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) All regimens used twice daily dosing, 2 weeks on/1 week off, unless otherwise noted.…”
Section: Safetymentioning
confidence: 99%
“…Although only limited data are available on the efficacy and safety of capecitabine monotherapy in China, several studies have suggested that it may be a suitable option for elderly patients with AGC [37][38][39][40]. In an RCT [38], 60 elderly stage II-III GC patients who had undergone dissection were randomly assigned to either high-dose capecitabine (2500 mg/m 2 b.i.d.…”
Section: Capecitabine Monotherapymentioning
confidence: 99%